Inovasi Desain Batik Kagunan Adi Wastra sebagai Representasi Identitas Institusional Fakultas Seni Rupa dan Desain ISI Surakarta - Agung Cahyana; Danang Priyanto; Danissa Dyah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: This community service activity is motivated by the absence of an institutional textile (wastra) that conceptually represents the academic, cultural, and scholarly identity of the Faculty of Fine Arts and Design (FSRD), Institut Seni Indonesia Surakarta. As an art-based higher education institution, FSRD requires a culturally grounded visual identity to strengthen its institutional image. This program aims to develop an innovative batik design titled Kagunan Adi Wastra that represents institutional identity and integrates academic, aesthetic, and cultural values. The subjects of this activity are the academic community of FSRD ISI Surakarta, who actively participated in the process. Method: The implementation employs a participatory art-creation approach, progressing through stages of exploration, incubation, conceptualization, and materialization, carried out through discussions, idea development, and collaborative design processes. Results: A batik motif that integrates the values of the Tridharma of Higher Education, symbols of art and design scholarship, and the ocean metaphor representing the vastness of knowledge. This activity provides institutional benefits by strengthening FSRD’s visual identity and social benefits by increasing awareness of cultural preservation through batik innovation. Conclusion: This program not only produces a batik design but also contributes to the development of a sustainable institutional identity rooted in local cultural values.